Design, Materials, Production, FEM and Experimental Analysis of an I.C. Engine Crankshaft – A Review (International Journal of Engineering and Computer Science, 2017)
A crankshaft can be called as the heart of any I.C. engine since it is the first recipient of the power generated by the engine. Its main function is to convert the oscillating motion of the connecting rod into rotary motion of the flywheel. Irrespective of having an intricate profile, crankshafts are mass produced. In this paper, the design considerations, finite element stress analysis and experimental stress analysis of the crankshaft are studied. The crankshaft of a mini truck, car and motorcycle was designed using standard design formulae, followed by the creation of its 3-D model using suitable design software like CATIA or PRO/E. Static and dynamic stress analysis was performed using ANSYS software to determine the values of total deformation and equivalent stress, based on which the areas susceptible to failure are identified. The analysis was carried out for commonly used materials for manufacturing a crankshaft, like cast iron and forged alloy steel. The work carried out by various researchers on design and FEM based analysis of a crankshaft is reviewed in this paper. Aspects such as materials, manufacturing processes, causes of failure, experimental stress analysis are also reviewed in this paper.